(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the knowledge of prison system staff in relation to the forms of transmission and prevention of tuberculosis. This is a descriptive, cross-sectional, field research, with a quantitative approach. A Knowledge, Attitude and Practice model questionnaire was used for data collection. Fifty-seven employees from prison system participated in the research. Of these, 32 reported never having participated in training courses that addressed the topic of tuberculosis and 39 did not consider themselves well informed about this disease. Some of the signs and symptoms of tuberculosis were correctly identified, while mistakes were observed regarding the form of prevention and transmission. There was a lack of information regarding tuberculosis. The acquisition of knowledge and daily life are essential for the effectiveness of the prison system servant as an active agent in the health-disease process of people deprived of their liberty.